Appraisal of composite's polymerization - A. A. Adamchik (Кубанский научный медицинский вестник, 2015)
Light curing composites are widely used in therapeutic dentistry when teeth are restored. But there are some complications that are connected with features of composite's polymerization. During this work it was made comparative analysis of polymerization's depth of different composite materials using halogen, diode and polyvalent polymerization apparatus with and without heating.